Penerapan Kanban pada Sistem Inventori PT FSCM Manufacturing Indonesia - Hans Thadeus; Tanti Octavia (Jurnal Titra, 2018)
FSCM Manufacturing Indonesia is a factory that focuses itself in producting otomotif filter. By this time, the factory has not implemented kanban thoroughly, thus, the inventory can not be controlled. The problem that occurs is all operators and employees do not responsible in the application of kanban in the factory. More over, there is a shortage of supporting material caused by unplanned inventory. This research is done to implement kanban and to control the supporting material at FSCM Manufacturing Indonesia. The result shows that kanban has been implemented and been controlled at the factory and the shortage of supporting material is also decreased from 30.577 materials to 2.185 materials.